Systemy zarządzania dokumentami elektronicznymi jako narzędzia zarządzania wiedzą - Wójtowicz, Radosław (Electronic documents management systems as knowledge management tools, 2005)
In the first part of the article is including describe of virtually projects conception. These projects beside classic characteristic this type of undertakings encompasses elements, witch shows directly into virtually nature. It's introduction to analyze of space from where knowledge can come, its sources and finnaly flow of information analyze in framework of the project's structure - between member of virtually team, information system and exterior sources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 331-338